COVID-19 in rural USA - Beth OConnor (James Cook University, 2023)
Introduction: In the rural areas of the USA, COVID-19 hit slower, spread faster, and was met with vaccine resistance. The presentation will provide an overview of the factors that contributed to a higher mortality rate in rural communities.Methods: Data on vaccine rates, infection spread, and mortality rates will be reviewed along with the healthcare system, economic, and social factors that created a unique situation in which infection rates in rural areas were similar, but death rates were nearly double that of their urban peers.Results: Participants will have a chance to learn how barriers in accessing health care, combined with rejection of public health guidelines, had tragic results.Discussion: Participants will have the opportunity to consider how public health information can be disseminated in a culturally competent manner that maximizes compliance for future public health emergencies.